Socializacija mladih skozi literarne pravljice - Burcar, Lilijana (Socialno delo, 2009)
Literary fairy-tales have functioned as an important tool in the ideological reproduction of gendered schemes and the naturalisation of patriarchal nuclear family.A survey of Charles Perrault's and the Grimm brothers' collections shows thet the role of the evil step-parent is alwayy assigned to the second wife or surrogate mother, while the biological mother comes to figure as a good mother only with her obligatory passage into death. Classic literary fairy-tales thus establish a narrative frame that requires biological mothers to be silenced, and surrogate mothers punished and destroyed, for the father to emerge as the nucleus of the heteronormative family unit. The father is established as a benevolent authority figure and absolved from the responsibility for his incestous acts or the cruelty he originally displayed in some folk tales. Most of the modern adaptations of classic literary fairy-tales continue to perpetuate this nuclear family pattern with the father figure functioning as the embodiment of indisputable authority and benevolence. With fairy-tales being one of the most ubiquitous genres for the young, this in turn has specific socialisation effects on young readers' perception and understanding of family units and kinship patterns.
Keywords: pravljice; mladi; socializacija; socialization; socialno starševstvo; biološko starševstvo